Generative and vegetative traits of the 'Granny Smith' apple grown under an anti-insect photoselective red net - Jemrić, Tomislav; Brkljača, Mia; Vinceković, Marko; Antolković, Ana Marija; Mikec, David; Vuković, Marko, inženjer hortikulture (2021)
Anti-insect photoselective nets present a new technology that combines light manipulation and pest protection in orchards. In this study, the effect of the anti-insect photoselective red net on the generative and vegetative traits was studied in an apple orchard near the city of Zadar, Croatia. 'Granny Smith' apples were grown on M9 rootstock and raised as slender spindles. The experiment consisted of two treatments: the trees covered with the red photoselective anti-insect nets (AGRITECH S. r. l., Eboli, Italy; mesh size of 2.4 × 4.8 mm) and uncovered trees as control. Yield, percentage of fruit with diameter >70 mm and fruit mass were not significantly different between treatments. L* color value was higher on fruit skin grown under the red net, and there was no significant difference in other color values (a*, b*, C* and h°). Soluble solids concentration (SSC) and total flavonoid content were significantly lower in fruit grown under red net than in control, and there was no significant difference in titratable acidity (TA), SSC/TA ratio, starch degradation and Streif maturity index. Red net proved to be effective against fruit red blush development (undesirable trait for 'Granny Smith' apple) and sunburn damage occurrence.
Protuinsektne fotoselektivne mreže predstavljaju novu tehnologiju koja istovremeno kombinira manipulaciju svjetlom i zaštitu od štetnika. U voćnjaku jabuka pokraj Zadra (Hrvatska) istraživan je utjecaj crvene protuinsektne fotoselektivne mreže na generativne i vegetativne parametre jabuke "Granny Smith". Jabuke su uzgajane na M9 podlozi te su imale uzgojni oblik vretenastoga grma. Istraživanje se sastojalo od dvaju tretmana: stabla prekrivena crvenom protuinsektnom fotoselektivnom mrežom (AGRITECH S. r. l., Eboli, Italija; veličina okca od 2.4 × 4.8 mm) i nepokrivena stabla kao kontrola. Prirod, udio plodova s promjerom >70 mm i masa plodova nisu se signifikantno razlikovali između tretmana. Jabuke uzgajane ispod crvene mreže imale su signifikantno veću L* vrijednost parametra boje kožice, dok za ostale parametre boje nije zabilježena signifikantna razlika (a*, b*, C* i h°). Sadržaj topljive suhe tvari (TST) i ukupni sadržaj flavonoida bio je signifikantno niži u jabukama uzgajanima ispod crvene mreže, dok nije zabilježen signifikantan utjecaj crvene mreže na titracijsku kiselost (TA), TST / TA, stupanj razgradnje škroba i indeks zrelosti (Streif). Primjena crvene mreže pokazala se vrlo djelotvornom u smanjenju pojavnosti dopunskoga crvenila (koje je kod jabuke "Granny Smith" nepoželjno svojstvo) i ožegotina od sunca na plodovima.
Bibliografija: 47 jed.
Summary ; Sažetak.
Keywords: Jabuke -- Granny Smith -- Kakvoća -- Štetnici -- Fotoselektivne mreže